Estratégias para a programação da produção em ambientes com capacidade flexível controlados pelo sistema PBC - Silva, Fábio Molina da (2014)
The PBC System is a well-known Ordering System that periodically syncronizes the material flow of the shop floor. The PBC has the property of constant and planned production lead-time, a policy of minimal lot sizing and a constant frequency on order releasing. An exhaustive literature review presented in this thesis has shown that work uses PBC when the production capacity is not constant. This is a reality presented in companies where compensatory times off allows the capacity be tranfer between time stamps and employees that can work on diferente positions, allowing the capacity to be managed from one working center to another. This work formally defines those issues using mathematical programming, and defines a set of heuristics to solve it. After the application of the models and heuristics to a set of instances, one can note that the heuristics are eficiente to solve the problem, and the strategy of using PBC is very successful in the studied environment (production system with variable capacity).